Electric Vehicle Routing Problem: A Review of Recent Approaches and Algorithms - Yingkai XU (Studia Universitatis Babes-Bolyai: Series Informatica)
With the rapid advancement of new energy vehicles, electric vehicles (EVs) have become integral to modern transportation systems. Compared with traditional fuel vehicles, EVs are limited by their limited battery capacity and require reasonable charging planning to complete the designated routes efficiently. Therefore, the effective routing of EVs has emerged as a critical research focus in transportation and logistics. This study comprehensively reviews recent advancements in the Electric Vehicle Routing Problem (EVRP) over the past three years. First, the concepts of EVRP are introduced. Then, the problem is classified according to energy consumption models, charging strategies, and constraints. Subsequently, various algorithms employed in these studies are analyzed and summarized. Finally, based on the current state of development in this field, the main challenges faced by EVRP and future research directions are discussed.